2008
DOI: 10.1080/19396360802102012
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Analysis ofIn VivoandIn VitroMatured Oocytes Derived from Naturally Cycling and Stimulated Mice

Abstract: The objective of the study was to analyze the potential role of follicle stimulating hormone (FSH) in cytogenetic changes of in vivo and in vitro matured mouse oocytes and to determine whether the lower developmental potential of immature oocytes is due to a higher incidence of abnormalities in meiotic spindle organization and chromosome alignment as well as aneuploidy. In vivo matured oocytes were collected from naturally ovulated and superovulated (5.0 I U of recombinant follicle-stimulating hormone [rec-FSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…FSH may rescue abnormal oocytes and facilitate the meiotic resumption of these oocytes, which otherwise may be destined for atresia (14). Recent data demonstrated no difference between exogenous FSH exposure and embryonic aneuploidy, which was compatible with our results (13,14,(16)(17)(18)(19). In our study, total FSH dose and cycle-day 3 FSH levels were similar in patients with abnormal and normal karyotypes.…”
Section: Discussionsupporting
confidence: 81%
“…FSH may rescue abnormal oocytes and facilitate the meiotic resumption of these oocytes, which otherwise may be destined for atresia (14). Recent data demonstrated no difference between exogenous FSH exposure and embryonic aneuploidy, which was compatible with our results (13,14,(16)(17)(18)(19). In our study, total FSH dose and cycle-day 3 FSH levels were similar in patients with abnormal and normal karyotypes.…”
Section: Discussionsupporting
confidence: 81%
“…In mouse oocytes matured in vitro (Roberts et al, 2005), exposure to elevated concentrations of FSH in culture is associated with increased aneuploidy and premature separation of sister chromatids. Another study (Xu et al, 2008), however, showed no difference between mature oocytes from natural cycles and immature oocytes, also from natural cycles, cultured in a solution of FSH and luteinizing hormone. A study in infertile women (Gras et al, 1992) compared aneuploidy rates in unstimulated cycles with aneuploidy rates in cycles stimulated with (i) human menopausal gonadotrophin (which contains FSH) and other hormones or (ii) a buserelin (GnRH agonist) flare.…”
Section: Discussionmentioning
confidence: 91%
“…In Xu et al (18), there is no difference between in vivo and in vitro matured oocytes derived from both naturally cycling and stimulated mice. Only a single dose of 5.0 IU of recombinant FSH was injected for the purpose of stimulation or FSH priming before IVM.…”
Section: Discussionmentioning
confidence: 96%